Ground-Based Remote Sensing of Aerosol Properties over a Coastal Megacity of Pakistan. (13th May 2018) - Tariq, Salman; Ul-Haq, Zia
Abstract : Atmospheric aerosols are considered to be an important constituent of Earth's atmosphere because of their climatic, environmental, and health effects. Therefore, while studying the global climate change, investigation of aerosol concentrations and properties is essential both at local and regional levels. In this paper, we have used relatively long-term Aerosol Robotic Network (AERONET) data during September 2006–August 2014 to analyze aerosol properties such as aerosol optical depth at 500 nm (AOD), Ångström exponent (440–870 nm) (AE), refractive index (RI), and asymmetry parameter over Karachi, a coastal megacity of Pakistan. The average annual values of AOD and AE were found to be 0.48 ± 0.20 and 0.59 ± 0.29, respectively. The peak (0.88 ± 0.31) AOD was recorded in July with corresponding AE of 0.30 ± 0.22 representing reasonably higher concentration of coarse size particles over Karachi. The cluster analysis using the scatter plot between absorption AE and extinction AE revealed that desert dust prevailed in the atmosphere of Karachi in spring and summer, while biomass burning aerosols dominate in autumn and winter. The peak values of volume concentrations of coarse and fine-mode particulate matter were found in summer and autumn, respectively. Also, we found significant growing trend in single-scattering albedo with wavelength, indicating the domination of dust particles during summer and spring. The peak value of the real part of the RI was observed in spring (1.53) and modest in winter (1.50). On the contrary, the peak value of the imaginary part of the RI was observed to be constantly elevated in winter and lesser in spring.